Pre-Service EFL Teachers’ Beliefs about Reflective Practice in the English Language Teacher Education Program: A Life History Study - Swara, Sanditya Jati; Ragawanti, Debora Tri (ETERNAL (English Teaching Journal), 2024)
This study examined pre-service EFL teachers’ beliefs about reflective practice in the English language teacher education program using a life history study. The study involved seven pre-service EFL teachers taking their master’s program in English language teacher education at a private university in Jawa Tengah, Indonesia. The research used a life history study which is a qualitative research design. The research instruments were reflective essays containing the past and present experience dealing with reflective practice, and a life history interview. The findings highlighted more positive beliefs than negative ones. Positive beliefs considered reflective practice effective for increasing EFL pre-service teachers’ pedagogical competence, critical thinking, and professional development. The negative beliefs viewed RP as time- and energy-consuming and could be confusing without any focus on writing.  As the pedagogical implication, reflective should focus on a particular issue, be guided with practical guiding questions, not be rigorous about how often and how to do it, and provide some alternatives based on the need and conditions of the (pre-service) EFL teachers.